2022
DOI: 10.1021/acs.macromol.1c02413
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-functionalized Porous Organic Polymers for Durable F-gas Capture from Semiconductor Etching Exhaust

Abstract: Efficiently capturing and recycling perfluorinated electron specialty gases (F-gases) with severe greenhouse effects (e.g., long atmospheric lifetime and high global warming potential) from etching exhaust is of great significance to the semiconductor industry. The adsorption separation technique based on a porous adsorbent is considered as an economical and effective method to remove the F-gases in the semiconductor exhaust, benefiting from its low energy consumption and high operational feasibility. Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…8,24,25 Also, the separation of CF 4 /N 2 and NF 3 /N 2 is more challenging than that of SF 6 /N 2 due to the smaller kinetic diameters of CF 4 and NF 3 (4.6 Å for CF 4 , 3.6 Å for NF 3 , 5.1 Å for SF 6 ). 26 Porous coordination polymers (PCPs) with emergence as promising porous materials, also called metal−organic frameworks (MOFs), have shown great promise in tackling several challenges like gas separation due to their surface functionalities and controllable pore sizes. 13,27−29 MOF-based separation of CF 4 /N 2 has been reported for limited MOFs, but few have been employed for a systematic separation of NF 3 /N 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,24,25 Also, the separation of CF 4 /N 2 and NF 3 /N 2 is more challenging than that of SF 6 /N 2 due to the smaller kinetic diameters of CF 4 and NF 3 (4.6 Å for CF 4 , 3.6 Å for NF 3 , 5.1 Å for SF 6 ). 26 Porous coordination polymers (PCPs) with emergence as promising porous materials, also called metal−organic frameworks (MOFs), have shown great promise in tackling several challenges like gas separation due to their surface functionalities and controllable pore sizes. 13,27−29 MOF-based separation of CF 4 /N 2 has been reported for limited MOFs, but few have been employed for a systematic separation of NF 3 /N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Pressure swing adsorption (PSA) based on adsorbents has shown advantages for gas separation due to its operational simplicity and energy efficiency. The adsorbent is the key to the PSA process, which is supposed to possess high capacity and selectivity . It has been reported that SF 6 capture and SF 6 /N 2 selectivity are high. However, the values of CF 4 sorption and CF 4 /N 2 selectivity are generally very low. ,, Also, the separation of CF 4 /N 2 and NF 3 /N 2 is more challenging than that of SF 6 /N 2 due to the smaller kinetic diameters of CF 4 and NF 3 (4.6 Å for CF 4 , 3.6 Å for NF 3 , 5.1 Å for SF 6 ) …”
Section: Introductionmentioning
confidence: 99%
“…A broad diffraction peak can be observed in the PXRD pattern, suggesting that Ppy-POF has a typical amorphous structure (Figure 1b). 50 The thermal gravimetric analysis (TGA) was performed to evaluate the thermal stability of Ppy-POF. According to the TGA result displayed in Figure 1c, the decomposition temperature of Ppy-POF in an air atmosphere is as high as 280 °C, indicating its high thermal stability.…”
Section: Resultsmentioning
confidence: 99%
“…The crystallinity of Ppy-POF was investigated by powder X-ray diffraction (PXRD). A broad diffraction peak can be observed in the PXRD pattern, suggesting that Ppy-POF has a typical amorphous structure (Figure b) . The thermal gravimetric analysis (TGA) was performed to evaluate the thermal stability of Ppy-POF.…”
Section: Resultsmentioning
confidence: 99%
“…However, it needs time to develop the structure, and the process accelerates with time, which is explained by a higher reactivity of the phenyl radical towards already attached phenyl groups than to the pure carbon surface. Another example of a process in which phenyl radicals do not undergo rapid reduction despite much more cathodic potential than thermodynamically required is cathodic polymerisation of 1,4‐diiodobenzene to polyphenylene on Si in acetonitrile, which also required longer time to proceed [22] …”
Section: Resultsmentioning
confidence: 99%